Single cell RNA sequencing after moderate traumatic brain injury: effects of therapeutic hypothermia - Nadine A. Kerr; James Choi; Simone Y. Mohite; Praveen Kumar Singh; Helen M. Bramlett; Jae K. Lee; W. Dalton Dietrich (Journal of Neuroinflammation)
Abstract Traumatic brain injury (TBI) initiates a cascade of cellular and molecular events that promote acute and long-term patterns of neuronal, glial, vascular, and synaptic vulnerability leading to lasting neurological deficits. These complex responses lead to patterns of programmed cell death, diffuse axonal injury, increased blood-brain barrier disruption, neuroinflammation, and reactive gliosis, each a potential target for therapeutic interventions. Posttraumatic therapeutic hypothermia (TH) has been reported to be highly protective after brain and spinal cord injury and studies have investigated molecular mechanisms underlying mild hypothermic protection while commonly assessing heterogenous cell populations. In this study we conducted single-cell RNA sequencing (scRNA-seq) on cerebral cortical tissues after experimental TBI followed by a period of normothermia or hypothermia to comprehensively assess multiple cell type-specific transcriptional responses. C57BL/6 mice underwent moderate controlled cortical impact (CCI) injury or sham surgery and then placed under sustained normothermia (37⁰C) or hypothermia (33⁰C) for 2 h. After 24 h, cortical tissues including peri-contused regions were processed for scRNA-seq. Unbiased clustering revealed cellular heterogeneity among glial and immune cells at this subacute posttraumatic time point. The analysis also revealed vascular and immune subtypes associated with neovascularization and debris clearance, respectively. Compared to normothermic conditions, TH treatment altered the abundance of specific cell subtypes and induced reactive astrocyte-specific modulation of neurotropic factor gene expression. In addition, an increase in the proportion of endothelial tip cells in the hypothermic TBI group was documented compared to normothermia. These data emphasize the importance of early temperature-sensitive glial and vascular cell processes in producing potentially neuroprotective downstream signaling cascades in a cell-type-dependent manner. The use of scRNA-seq to address cell type-specific mechanisms underlying therapeutic treatments provides a valuable resource for identifying targetable biological pathways for the development of neuroprotective and reparative interventions.